Social Enterprises: Beyond the Hype - Quek, Sean (Institutional Knowledge at Singapore Management University, 2008)
With their promises of sustainability, social integration and lower dependence on welfare, social enterprises are the flavour of the month. But, as Sean Quek points out, the challenges involved in designing and executing a sustainable social enterprise are often underestimated.